2021
DOI: 10.1080/20961790.2021.1889136
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of anatomy to forensic sex estimation: focus on head and neck bones

Abstract: This study sought to provide an up-to-date review of the importance of anatomy to human identification, focusing on the usefulness of anatomical knowledge about the head and neck bones and teeth to sex estimation in routine forensic anthropology methods. A detailed search of osteology applications in forensic sex estimation was conducted through the electronic databases for the 10 years prior to July 2020. Relevant articles and classic literature on the subject were gathered and are outlined in this review. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 106 publications
1
10
0
Order By: Relevance
“…The κ coefficient was 0.83. This result was comparable to that of another study (Mello-Gentil and Souza-Mello, 2022).…”
Section: Reproducibility Of Measurement and Morphological Evaluationsupporting
confidence: 91%
“…The κ coefficient was 0.83. This result was comparable to that of another study (Mello-Gentil and Souza-Mello, 2022).…”
Section: Reproducibility Of Measurement and Morphological Evaluationsupporting
confidence: 91%
“…In this study, almost all the cranial variables were significant for population [ 12 ]. Estimation of population is linked to sex and for this reason sex determination is often the first step in the identification process [ 44 ]. A South African study by Işcan and Steyn showed that the crania are more discriminatory than the mandibles especially in females [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these structures were chosen not only to test these relationships but also because they represent different muscles and ligaments that move and/or stabilise the head and neck (Houseman et al, 2000; Sinnatamby & Last, 2011; Standring, 2021), which may contribute to overall skeletal robusticity. Although interdisciplinary research across anatomy and anthropology is important (Mello‐Gentil & Souza‐Mello, 2021; Rissech, 2021), no existing research has assessed sexual dimorphism and population variation of the soft tissues and entheses of the head and neck. Therefore, this paper aims to present architectural data and analyse sex and population differences in cervical soft tissues (muscles and ligaments) and entheses related to these cranial and clavicular landmarks.…”
Section: Introductionmentioning
confidence: 99%